Volume 2: Aircraft Engine; Marine; Microturbines and Small Turbomachinery 1992
DOI: 10.1115/92-gt-083
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Compressor Rotor Tip Crops on Turboshaft Engine Performance

Abstract: The results from an experimental study into the effect of compressor rotor tip clearance changes on the steady-state performance and stability margins of a free-power turbine turboshaft engine are presented and discussed. This work was directed at the development of methods to diagnose engine condition from gas path measurements. It was found that the normal production suite of engine instrumentation was able to measure the deterioration in engine performance due to the implanted compressor degradation and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Changes in surface quality and airfoil geometry reduce efficiency and work capability of the stage. Increased clearances reduce surge margin, reduce the efficiency, cause a reduction in stage work, and reduce the compressor flow capacity (Kurz and Brun, 2001;Spakovszky et al, 1999;Graf et al, 1998;Smith and Cumpsty, 1984;Frith, 1992).…”
Section: Degradation Of Componentsmentioning
confidence: 99%
“…Changes in surface quality and airfoil geometry reduce efficiency and work capability of the stage. Increased clearances reduce surge margin, reduce the efficiency, cause a reduction in stage work, and reduce the compressor flow capacity (Kurz and Brun, 2001;Spakovszky et al, 1999;Graf et al, 1998;Smith and Cumpsty, 1984;Frith, 1992).…”
Section: Degradation Of Componentsmentioning
confidence: 99%
“…This is mainly due to the leakage flow from pressure surface to the suction surface through the tip clearance area. Frith [180] Compressor A 3% tip clearance increase on the axial compressor stages decreases flow capacity by 4.6% and drops the pressure ratio by 3%, and decrease in compressor efficiency by 2.5%. Melcher and Kypuros [181] Turbine A 0.25mm change in turbine tip clearance may cause up to 10°C engine exhaust gas temperature and decrease turbine efficiency up to 1.3% Radtke and Dibelius [182] Turbine…”
Section: F) Thermal Distortionmentioning
confidence: 99%
“…Meanwhile, a slight surge of blades will occur, which will affect the engine's stability. 4 A simulation result showed that compared with configuration 1, which has a small tip clearance of multistage high-pressure compressor, configuration 2, which has a large tip clearance of multistage high-pressure compressor, causes the stable operating range to be reduced by 40%, and the efficiency and pressure ratio are also decreased by 1.5% and 2%, respectively. 5 In addition, the blade tip-clearance changes have a great impact on the rate of fuel consumption.…”
Section: Introductionmentioning
confidence: 99%